Pengembangan Lerak (Sapindus Rarak DC) sebagai Bahan Irigasi Saluran Akar Berdasarkan Teknologi Nano - Edi Satria; Nevi Yanti (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Biocompatibility is a major problem in today's world, so the World Health Organization (WHO) recommends returning to nature. In dentistry, one of the natural ingredients that can be used as an alternative irrigation material is soapberry fruit extract (Sapindus rarak DC). Research has shown that soapberry extract can remove the smear layer from the root canal, has antimicrobial effects, and has low surface tension. Root canals irrigated with soapberry extract solution have lower dentin surface porosity and higher tooth strength compared to a combination solution of NaOCl + EDTA. Previous studies have shown that soapberry irrigation materials in the form of micro-particles cannot completely clean the smear layer in the apical third. Purpose: The purpose of this literature review is to review the use of soapberry (Sapindus rarak DC) using nanotechnology as a nanotechnology-based irrigation material for root canal treatment. This study is a literature review using a search method for articles that have passed the publication process of publications published in 2015-2024 which can be accessed in full text in pdf and scholarly formats. Conclusion: To achieve a clean smear layer in the apical third, it is necessary to develop a soapberry irrigation material in the form of nanoparticles. The material in the form of nanoparticles has the advantage of strengthening the antimicrobial and anti-inflammatory effects of Sapindus rarak DC, as well as allowing effective delivery of active substances into the root canal of the tooth.